Evolutionary heritage influences Amazon tree ecology - Coelho de Souza, Fernanda; Dexter, Kyle G.; Phillips, Oliver L.; Brienen, Roel J.W.; Chave, Jerome; Galbraith, David R.; Lopez Gonzalez, Gabriela; Monteagudo Mendoza, Abel; Pennington, R. Toby; Poorter, Lourens; Alexiades, Miguel; Álvarez-Dávila, Esteban; et al. (Royal Society, 2016)
Lineages tend to retain ecological characteristics of their ancestors through time. However, for some traits, selection during evolutionary history may have also played a role in determining trait values. To address the relative importance of these processes requires large-scale quantification of traits and evolutionary relationships among species. The Amazonian tree flora comprises a high diversity of angiosperm lineages and species with widely differing life-history characteristics, providing an excellent system to investigate the combined influences of evolutionary heritage and selection in determining trait variation. We used trait data related to the major axes of life-history variation among tropical trees (e.g. growth and mortality rates) from 577 inventory plots in closed-canopy forest, mapped onto a phylogenetic hypothesis spanning more than 300 genera including all major angiosperm clades to test for evolutionary constraints on traits. We found significant phylogenetic signal (PS) for all traits, consistent with evolutionarily related genera having more similar characteristics than expected by chance. Although there is also evidence for repeated evolution of pioneer and shade tolerant life-history strategies within independent lineages, the existence of significant PS allows clearer predictions of the links between evolutionary diversity, ecosystem function and the response of tropical forests to global change.